2018
DOI: 10.1117/1.nph.5.2.025010
|View full text |Cite
|
Sign up to set email alerts
|

Which is more costly in Chinese to English simultaneous interpreting, “pairing” or “transphrasing”? Evidence from an fNIRS neuroimaging study

Abstract: This study examined the neural mechanism underlying two translation strategies associated with Chinese to English simultaneous interpreting (SI) targeting the left prefrontal cortex (PFC), which is generally involved in the control of interference and conflict resolution and has been identified as the brain area that plays a pivotal role in SI. Brain activation associated with the two strategies including "pairing" and "transphrasing" were compared with that from "nontranslation," which keeps the source langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Slow changes and shifts in the size and center of activation regions over time were observed in the dynamic brain activation map of motor and auditory cortical regions, respectively. A similar phenomenon was observed in the dynamic brain activation maps of pairing and transphrasing stimuli in Lin et al's study of fNIRS-based Chinese-English simultaneous interpretation (Lin et al, 2018 ). These changes in neural activation patterns were also studied in simulations by Li et al ( 2017 ).…”
Section: Introductionsupporting
confidence: 75%
“…Slow changes and shifts in the size and center of activation regions over time were observed in the dynamic brain activation map of motor and auditory cortical regions, respectively. A similar phenomenon was observed in the dynamic brain activation maps of pairing and transphrasing stimuli in Lin et al's study of fNIRS-based Chinese-English simultaneous interpretation (Lin et al, 2018 ). These changes in neural activation patterns were also studied in simulations by Li et al ( 2017 ).…”
Section: Introductionsupporting
confidence: 75%
“…Over the last decade, scholars in translation studies as well as from other fields have applied the above-mentioned cross-disciplinary theories and methodologies to investigate translation processes. Recent efforts have been invested to such topics related to TPR as cognitive effort (Lin et al, 2018), attention or working memory (Kosma, 2007), emotion (Hubscher-Davidson, 2018), creativity (Cho, 2006), and translation competence (Sickinger, 2017), to name just a few. TPR has seen an upsurge over time, as evidenced by numerous publications in various forms (e.g., monographs, edited books, and journal articles Sun and Xiao, 2019).…”
Section: Translation Process Researchmentioning
confidence: 99%
“…Although it has been suggested that investigating the neural mechanisms of interpreting would benefit the area of neurolinguistics as a whole ( García, 2013 ), these remain scarcely investigated. Of the existing neurolinguistic research on interpreting, the majority are localization studies using functional magnetic resonance imaging ( Lehtonen et al, 2005 ; Elmer, 2016 ; Elmer et al, 2014 ; Hervais-Adelman et al, 2015a , b , 2017 ; Zheng et al, 2020 ), positron emission tomography ( Klein et al, 1995 ; Price et al, 1999 ; Rinne et al, 2000 ; Tommola et al, 2000 ), functional near-infrared spectroscopy ( Quaresima et al, 2002 ; Lin et al, 2018a , b ; Ren et al, 2019 ), and diffusion tensor imaging ( Van de Putte et al, 2018 ). Though findings vary, brain structures that have been consistently identified as being involved in interpreting include the dorsolateral prefrontal cortex, pars triangularis and supramarginal gyrus.…”
Section: Introductionmentioning
confidence: 99%